Optimizing Outpatient Prescriptions Through Smarter Drug Substitution Strategies (The Science Post, 2025)
Optimizing outpatient prescriptions is a growing challenge in healthcare systems due to rising drug costs, supplychain disruptions, and the need for equitable access to essential medicines. Smarter drug substitution strategies—suchas generic substitution, therapeutic interchange, and algorithm-driven decision support—offer promising solutions toreduce costs while maintaining treatment efficacy and patient safety. This paper examines the role of substitutionframeworks in outpatient care, highlights the economic and clinical rationale behind substitution, and discusses digitaland policy-based enablers that can standardize the practice. By leveraging artificial intelligence, real-time prescriptionmonitoring, and evidence-based guidelines, outpatient systems can balance cost efficiency with improved healthoutcomes. The findings underscore that substitution must be carefully integrated into prescribing workflows withconsideration for patient trust, regulatory environments, and long-term health system sustainability